Gender Equality and Women Empowerment in The National Development of Indonesia - Siscawati, Mia; Adelina, Shelly; Eveline, Ruth; Anggriani, Septiani (Journal of Strategic and Global Studies, 2020)
Gender Equality and Women Empowerment has been part of the National Long-Term Development Plan (Rencana Pembangunan Jangka Panjang/RPJP) of Indonesia for the period of 2000 – 2025. Every five year the national government of Indonesia prepares the National Medium-Term Development Plan (Rencana Pembangunan Jangka Menengah Nasional/RPJMN). This paper explores the status of gender equality and women empowerment in the national development of Indonesia, especially during the period of the implementation RPJMN of 2015 - 2019. This paper consists of review of national development policies, analysis of situations and problems related to gender equality and women empowerment, and achievements of gender mainstreaming in development of various sectors during the implementation of RPJMN of 2015-2019. It also delivers recommendations for direction of policies and programs for the next national medium-term development plan (RPJMN of 2020 – 2024). Data for this paper are derived from reviewing policy documents, official reports of ministries and government agencies, analyzing official statistical data and other secondary data from various sources.